2013
DOI: 10.1021/ie4009327
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanorods from Food Industrial Waste and Their Application in Improving the Keeping Quality of Milk

Abstract: A novel method for the synthesis of silver nanorods is reported, in which industrial milk waste was utilized, that were then used to extend the stability of milk. During the synthesis, the size of the silver nanorods were affected by pH and temperature. Silver nanorods were formed at alkaline pH in room temperature, whereas nanoparticles were formed in lower pH at elevated temperature. The obtained nanostructures were characterized by UV−visible spectrophotometer, energy dispersive Xray analysis (EDAX), and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has been reported that there are various chemical reduction methods to load silver nanoparticles on the composite materials [27][28][29][30]. However, the silver nanoparticles were protected and loaded on iron oxides hollow microspheres to form Ag/α-Fe 2 O 3 by UV irradiation without any additional reducing agents or initiators in our research.…”
Section: Introductionmentioning
confidence: 71%
“…It has been reported that there are various chemical reduction methods to load silver nanoparticles on the composite materials [27][28][29][30]. However, the silver nanoparticles were protected and loaded on iron oxides hollow microspheres to form Ag/α-Fe 2 O 3 by UV irradiation without any additional reducing agents or initiators in our research.…”
Section: Introductionmentioning
confidence: 71%
“…[ 577 ] Silver nanorods were synthesized from AgNO 3 in the presence of industrial milk waste, containing lactose and whey as reducing and stabilizing agents, respectively. [ 578 ] The silver nanostructures were non‐cytotoxic (to three human cell lines) and could be used to extend the milk shelf‐life by controlling microbial growth. [ 578 ] Such waste‐originated nanoparticles can be combined with biopolymers into bioplastics for smart packaging applications.…”
Section: Emerging Applications Of Flw Bioplasticsmentioning
confidence: 99%
“…[ 578 ] The silver nanostructures were non‐cytotoxic (to three human cell lines) and could be used to extend the milk shelf‐life by controlling microbial growth. [ 578 ] Such waste‐originated nanoparticles can be combined with biopolymers into bioplastics for smart packaging applications.…”
Section: Emerging Applications Of Flw Bioplasticsmentioning
confidence: 99%
“…For example, Costa and coworkers [ 188 ] prepared and used silver-montmorillonite (Ag-MMT) in packaging for freshly-sliced fruit salads, and found inhibition of microbial growth and increased shelf life. In another interesting work, Sivakumar and colleagues [ 189 ] showed a new method to produce nontoxic silver nanorods from dairy industry waste. They used them to control bacterial growth in milk during processing and storage, thus demonstrating extension of milk shelf-life.…”
Section: Agnps In Food Packagingmentioning
confidence: 99%